Europeanization of energy and climate policy new trends and their implications for the German energy transition process - Tews, Kerstin (Freie Univ. Berlin, Forschungsstelle für Umweltpolitik (FFU), 2014)
In this paper I discuss very recent developments in the post-2020 climate and energy policy framework of the European Union as well as their implications for the German energy transition process. In a first step, I analyze how the need for the planned modifications of the European strategy is framed. I argue that the European Commission obviously sparked off a new round in tackling a longstanding governance dilemma between European market integration and regulatory diversity among Member States regarding energy and environmental issues. In a second step, I take a closer look at the implications of these changes at the European level for the German energy transition pathway. I argue that supranational pressure to adapt national energy policies to internal market rules coincides with the dominant domestic framing of the need for market integration of renewable energies. This interplay of problem framings, on the one hand, and the discretionary power of the European Commission to control competition rules, on the other, explains the very recent instrumental shift in the German national support scheme for renewable energies. Subsequently, I debate various governance options for dealing with the implications of the proposed new European approach to energy and climate policy, both against the backdrop of the particular German way of energy transition as well as against the backdrop of general transition challenges.
Keywords: Europäische Union; Energiewende; Klimaschutz; Deutschland